2017
DOI: 10.1038/s41598-017-01754-9
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to dietary conditions by trehalose metabolism in Drosophila

Abstract: Trehalose is a non-reducing disaccharide that serves as the main sugar component of haemolymph in insects. Trehalose hydrolysis enzyme, called trehalase, is highly conserved from bacteria to humans. However, our understanding of the physiological role of trehalase remains incomplete. Here, we analyze the phenotypes of several Trehalase (Treh) loss-of-function alleles in a comparative manner in Drosophila. The previously reported mutant phenotype of Treh affecting neuroepithelial stem cell maintenance and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 53 publications
(91 reference statements)
3
46
0
Order By: Relevance
“…Moreover, trehalose is the main insect hemolymph sugar in some insects, and is important in maintaining a number of physiological processes such as providing energy for flight muscles and protecting insects against low temperatures . The loss of trehalase was lethal to fruit flies at the pupal stage, and the decrease of trehalase could affect the supply of energy in S. zeamais .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, trehalose is the main insect hemolymph sugar in some insects, and is important in maintaining a number of physiological processes such as providing energy for flight muscles and protecting insects against low temperatures . The loss of trehalase was lethal to fruit flies at the pupal stage, and the decrease of trehalase could affect the supply of energy in S. zeamais .…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the cause of larval lethality, we then investigated whether glycogen mutants exhibit sensitivity to malnutrition. We previously reported that Tps1 mutants are sensitive to sugar deprivation and poor dietary conditions (Matsuda et al, 2015;Yasugi et al, 2017). However, larval lethality in GlyS and GlyP mutants was not changed under a yeast-only (Y-only) diet that largely lacks carbohydrates compared with that of mutants on a normal diet (ND) (Fig.…”
Section: Larval Lethality In Glycogen Mutants Is Partly Rescued By Enmentioning
confidence: 93%
“…Drosophila were reared on fly food (normal diet, ND) containing 8 g agar, 100 g glucose, 45 g dry yeast, 40 g corn flour, 4 ml propionic acid and 0.45 g butylparaben (in ethanol) per liter (1× recipe). For the analysis of restricted or enriched dietary conditions, fly food was prepared as described previously (Matsuda et al, 2015;Yasugi et al, 2017). In brief, fly food containing a reduced or increased amount of yeast or glucose was used (0.2× or 2× the amount used for the 1× recipe).…”
Section: Fly Foodmentioning
confidence: 99%
See 2 more Smart Citations